A NEW REGIONAL APPROACH FOR FREE DISTRIBUTED PARAMETER SYSTEMS - Al-Jawari, Naseif (Iraqi Journal of Science, 2024)
The aim of this paper is to develop a new approach based on state exponential estimator. More precisely, we extend the notion of regional exponential observability as in ref. [1] to the case where the dynamical systems are uncontrolled (F-systems). For different sensors, we give the characterizations of regional exponential free observer in order that exponential free observability can be achieved. Furthermore, we show that, there exists a dynamical F-system for distributed diffusion F-system is not exponential F-observable in the usual sense, but it may be regional exponential F-observable.